2019
DOI: 10.1177/0361198119844751
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of In-Vehicle Lane Departure Warning System using Standard Global Positioning System Receiver

Abstract: A lane departure warning system is a critical element among advanced driver-assistance systems functions, which has significant potential to reduce crashes. Generally, lane departure warning systems use image processing or optical scanning techniques to detect a lane departure. These systems have some limitations, however, such as harsh weather or irregular lane markings having a negative influence on their performance. Integrating global positioning system (GPS) and digital maps of lane-level resolution with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Hu et al (2017) investigated drivers' behavior in unintentional lane departure to assist in the design of LDWS to reduce false alarms. Faizan et al (2019) found that LDWS performance was improved by using GPS information rather than a camera based system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hu et al (2017) investigated drivers' behavior in unintentional lane departure to assist in the design of LDWS to reduce false alarms. Faizan et al (2019) found that LDWS performance was improved by using GPS information rather than a camera based system.…”
Section: Literature Reviewmentioning
confidence: 99%